2-Amino-3-nitropyridinium hydrogen oxalate - Akriche, Samah (International Union of Crystallography, 2009)
In the non-centrosymetric title compound, C(5)H(6)N(3)O(2) (+)·C(2)HO(4) (−), the hydrogen oxalate anions form corrugated chains parallel to the c axis, linked by O—H⋯O hydrogen bonds. The 2-amino-3-nitropyridinium cations are anchored between theses chains by N—H⋯O and C—H⋯O hydrogen bonds and van der Waals and electrostatic interactions, creating a three-dimensional network.